What does the development of medical tourism in Barbados hold for health equity? an exploratory qualitative case study. Issue 1 (December 2017) - Labonté, Ronald; Runnels, Vivien; Crooks, Valorie; Johnston, Rory; Snyder, Jeremy
Abstract Background Although the global growth of privatized health care services in the form of medical tourism appears to generate economic benefits, there is debate about medical tourism's impacts on health equity in countries that receive medical tourists. Studies of the processes of economic globalization in relation to social determinants of health suggest that medical tourism's impacts on health equity can be both direct and indirect. Barbados, a small Caribbean nation which has universal public health care, private sector health care and a strong tourism industry, is interested in developing an enhanced medical tourism sector. In order to appreciate Barbadians' understanding of how a medical tourism industry might impact health equity. Methods We conducted 50 individual and small-group interviews in Barbados with stakeholders including government officials, business and health professionals. The interviews were coded and analyzed deductively using the schedule's questions, and inductively for novel findings, and discussed by the authors. Results The findings suggest that in spite of Barbados' universal health care and strong population health indicators, there is expressed concern for medical tourism's impact on health equity. Informants pointed to the direct ways in which the domestic population might access more health care through medical tourism and how privately-provided medical tourism in Barbados could provide health benefits indirectly to the Barbadian populations. At the same time, they cautioned that these benefits may not materialize. For example, the transfer of public resources — health workers, money, infrastructure and equipment — to the private sector to support medical tourism with little to no return to government revenues could result in health inequity through reductions in access to and availability of health care for residents. Conclusions In clarifying the direct and indirect pathways by which medical tourism can impact health equity, these findings have implications for health system stakeholders and decision-makers in Barbados and other countries attempting both to build a medical tourism industry and to protect health equity.